Studi Karakterisasi Sintesis Nano Partikel ZnO Menggunakan Metode Kopresipitasi dengan Varian Konsentrasi Dopping Cu - Radityo Rangkuti; Heru Harsono; Muhammad Ghufron (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2018)
Syntesis of ZnO nano particles using co-precipitation methode with variation of cu-doped consentrate has been done. This research devided by two part, the first part is syntesis process, and the second part is characterization process. The first step of synthesis process is by measuring Zn assetate and CuS mass to get variation of Cu –Doped consentration which is 0%, 2%, 4%, 6%, and 8%, then dissolved it with 150 ml HCl 0.5 M. The next step is by droping on solution slowly until pH 10, then the solution stired on a hotplate for 3 hours with 60⁰ C temprature. Next, the synthesis proceed is done after following this procees which is preticipation, purification, and drying with 150⁰ C. Characterization proses has been done by using SEM-EDX and XRD. Ressult by using XRD ZnO phase found in 0%, 4%, 6%, and 8% Cu-doped. The smallest average of diameter crystallin acquaired from a sampel without Cu-doped which is 29 nm, and the largest is acquaired from a sampel with 8% Cu-doped which is 37 nm. SEM-EDX result shown particles morfology and the persentage of mass and atom. As it result can be concluded The persentage of mass and atom Cu greater along the consentration